PERBAIKAN KEMASAN DAN PELABELAN PRODUK KRIPIK SINGKONG MADURA UNTUK MEWUJUDKAN PELAKU USAHA MANDIRI MENYONGSONG TANTANGAN MASYARAKAT EKONOMI ASEAN YANG BERKELANJUTAN - R.P. Much. Muchtar; Hidayat Andyanto; Moh. Zainudin (Jurnal ABDIRAJA, 2018)
The purpose of Science and Technology PLUS activities for the community is to improve the packaging and labeling of Kripik Singkong Madura Kipik Terbang Kuda Cassava Chips in Lanjuk Village, Manding District and Kripik Singkong Cap Baby in Pamolokan Village, Sumenep Sub-District, Sumenep Regency to realize independent business people to meet the challenges of a sustainable ASEAN economic community. The targets to be achieved are: a) Market-worthy modern packaging products with aluminum foil or appropriate plastic packaging, b) Labels include DINKES permits and MUI halal certification in accordance with regulatory provisions, c) Labels include product names, list of materials used and weight clean or clean contents in accordance with the provisions of the regulations, and d) Cassava chips business actors begin to be independent and ready to meet the challenges of the ASEAN Economic Community. The response of cassava chips entrepreneurs is quite varied, but there are also those who are appreciative and positive. Variation responses are, there are those who respond suspiciously, lack of appreciation and even tend to be "reluctant". After the entrepreneur follows the coaching, counseling, and coaching intensely and effectively with "face to face" and training, the entrepreneur is motivated to produce and improve the packaging and label of the cassava chips, and even dynamic packaging is always expected to change and grow. And even with improvements in packaging and labeling, they want to be able to penetrate a broader market, not just the local market.